Building Students’ Learning Autonomy through Collaborative Learning to Develop Their Language Awareness - Zefki Okta Feri; Rita Erlinda (Proceedings of ISELT FBS Universitas Negeri Padang, 2014)
Language awareness is defined as a person’s sensitivity to and conscious awareness of the nature of language and its role in human life. It refers to the development in learners of enhancing consciousness and sensitivity to the form and function of the language itself. Students’ language awareness is very important to be developed as it contributes much towards students on how they should learn the language, being well-motivated and how they come into language comprehensively. The activity of students’ learning in the classroom typically seems to concern with learning which they need to learn for achievement of life goals than being aware of what they learn. This is exactly what happened in learning English as a foreign language for Indonesian students. They seem to not have any responsibility for their own learning. This paradigm makes students become more less-motivated and increase their passivity. Students need to develop their own learning strategies so that as far as possible to be autonomous learners. Students having learning autonomy tend to be more competitive in learning because they have a capacity for detachment, critical reflection, decision making and independent actions. This autonomy enables students to develop their own potential. The widespread of autonomy provides an environment which stimulates students’ critical self-awareness. It also supports awareness-raising about the nature of languages, cultures and language learning. Collaborative learning seems to be one effective teaching technique to foster learners’ autonomy. This paper aims to promote the idea of how to build students’ learning autonomy though collaborative learning to develop their language awareness.